Body Dissatisfaction Among Adolescents Receiving Health Services at Payaman Community Health Center - Aini, Dwi Fitria; Suhadianto (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The phenomenon of body dissatisfaction has increasingly appeared among adolescents, especially in the era of social media that emphasizes certain beauty standards. This study aims to understand the psychological dynamics of body dissatisfaction in an adolescent receiving health services at Payaman Community Health Center and to describe effective psychological interventions to help the client overcome this issue. The research employed a qualitative single-case study approach, with data collected through interviews, observations, and psychological assessments, including graphic tests (HTP and DAP) and the Depression Anxiety Stress Scale (DASS-42). The assessment results indicated recurring negative thought patterns regarding body image, feelings of inferiority, and a tendency toward social withdrawal. The intervention was conducted using a Cognitive Behavioral Therapy (CBT) approach, through stages of identifying negative thoughts, cognitive restructuring, developing positive self-talk, and implementing more adaptive behaviors. The intervention results showed increased self-awareness and more realistic thinking patterns. The client began to distinguish between facts and assumptions, develop positive alternative thoughts, and demonstrated improvements in self-confidence and self-acceptance. This study concludes that CBT-based interventions are effective in reducing body dissatisfaction among adolescents, particularly when accompanied by social and family support.